SYSTEMIC AGENCY IN EDUCATION IN EXTRAORDINARY CIRCUMSTANCES: CHALLENGES ENCOUNTERED BY LF NIŠ DURING THE COVID-19 PANDEMIC AND OPPORTUNITIES FOR DEVELOPING SYSTEMIC AGENCY IN LEGAL EDUCATION: Challenges encountered by LF Niš during the COVID-19 pandemic and opportunities for developing systemic agency in legal education - Ignjatovic, Gordana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
Systemic Agency is the capacity of the system as a whole to respond to emerging issues by relying on the collective intelligence and joint action of all stakeholders involved in system processes. This paper explores the systemic agency of participants in legal education at the Law Faculty in Niš during the COVID-19 pandemic (2020-2022), when higher education fully resorted to online instruction. The first part of the paper outlines the conceptual framework of systemic agency. The second part briefly presents the initial institutional response and educational circumstances at the outset of the pandemic in Serbia. The third part examines the challenges encountered by LF Niš students and teachers, and observed benefits of e-learning, by analyzing the empirical research results of several surveys conducted at LF Niš in this period. Based on these insights, the author reviews the opportunities for improving the systemic agency of core stakeholders and the system as a whole for prospective e-learning purposes. Attempting to record the first teaching/learning experience at LF Niš fully conducted online, the author emphasizes the potentials of online/hybrid learning in legal education and promotes joint action in developing a more responsive, supportive and efficient systemic approach applicable in both regular and extraordinary circumstances.